IMPLEMENTASI SOCIAL LEARNING THEORY DALAM MENGATASI PERILAKU INDISIPLINER SISWA KELAS XI IIS - Lestari, Tri Indah; Sulistyarini, Sulistyarini; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the implementation of Social Learning Theory in the process of attention, retention, production, and motivational in overcoming the indisciplinary behavior. The data source of this research is a sociology teacher and students of class XI IIS SMA Muhammadiyah 2 Pontianak. The research approach is qualitative with descriptive method. Data collection techniques are interviews, observations, documentation. Data collection tools are interview guidelines, observation guidelines, field notes and archives, documentation. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The results of this study indicate that informan AP as a sociology teacher has implemented Social Learning Theory based on the Attention, Retention, Production, and Motivation processes. This is evidenced in the Attention process, namely the teacher attracts students' attention when about to start learning, maintains students attention during learning and gives attention to indisciplinary students. In the Retention process the teacher repeats the learning of the previous meeting, provides tests and quizzes, presents material using interesting and relevant media. In the Production process, teachers invite students to discuss and ask about parts of the material they do not understand, and give assignments. In the motivation process the teacher provides encouragement and appreciation to students.